The Exercise of Moral Imagination in Stigmatized Work Groups - Roca, Esther (Journal of business ethics, 2010)
This study introduces the concept of moral imagination in a work context to provide an ethical approach to the controversial relationships between dirty work and dirty workers. Moral imagination is assessed as an essential faculty to overcome the stigma associated with dirty work and facilitate the daily work lives of workers. The exercise of moral imagination helps dirty workers to face the moral conflicts inherent in their tasks and to build a personal stance toward their occupation. Finally, we argue that organizations with dirty work groups should actively adopt measures to encourage their employees’ exercise of moral imagination. This study investigates how organizations might create conditions that inspire moral imagination, particularly with regard to the importance of organizational culture as a means to enhance workers’ moral sensitivity. Furthermore, this investigation analyzes different company practices that may derive from a culture committed to moral imagination.